Coinoculação de rizobactérias com Bradyrhizobium japonicum na mitigação dos efeitos do La Niña na cultura da soja - Spanevello, Janaina de Fatima (2023)
Population growth and the need to produce food with food security is a global problem. The use of bioinputs based on bacteria that promote plant growth becomes a sustainable alternative for agricultural production. However, the simultaneous use of several species of microorganisms and the lack of bioinput dose control may not bring beneficial results for the soybean crop. The objective of this research was to evaluate the use of species of microorganisms and application rates in the coinoculation of soybean crops. In the first harvest, 2021/2022, seven experiments were carried out using the microorganisms Bradyrhizobium japonicum, Azospirillum brasilense, Pseudomonas fluorescens, Bacillus subtilis, Bacillus aryabhattai and Bacillus megaterium in sowing furrows and in foliar spraying. In the second year, 2022/2023, an experiment was carried out with the best treatments from the previous year, with the microorganisms applied in the sowing furrow. Characteristics related to the percentage of soil cover, leaf area index, number and dry mass of nodules, surface area, volume and length of roots, grain yield and mass of a thousand grains were evaluated in both years. Furthermore, a laboratory experiment was carried out, in 2023, the order to test the bacteria used in the field experiment, under isolated and combined conditions, evaluating the growth of the bacterial colony. Under the tested conditions, the application of growth-promoting bacteria promoted the maintenance of plant growth and development even in the two years with the presence of water deficit. The foliar application of the microorganisms did not promote an increment for the variables, under the conditions of the study. In both seasons, treatments with co-inoculation of Bradyrhizobium japonicum (2L) + Bacillus subtilis (2L) and Bradyrhizobium japonicum (2L) + Bacillus aryabhattai (0.1L) were superior, confirming that such combinations did not have significant interaction in the laboratory experiment. Thus, they can be used in coinoculation in the soybean crop.